Anaesthetic Awareness: A Past, Present and Future Challenge - Shanahan, Daire (Trinity Student Medical Journal, 2015)
Anaesthetic awareness is a rare complication of general anaesthesia. Its occurrence is likely to be multifactorial, with young age, female sex, Chinese ethnicity, previous awareness, gestation, and pulmonary hypertension associated with a higher risk of awareness. Awareness is a distressing complication for patients, with 30% of patients who experience awareness developing psychiatric symptoms ranging from nightmares, flashbacks, and anxiety to post-traumatic stress. Therefore, attempts to monitor awareness are desirable. The aim of this short article is to look at past achievements and future challenges in detecting, monitoring, managing and avoiding awareness.